2022
DOI: 10.1007/s13555-022-00799-7
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Androgenetic Alopecia: A Comprehensive Review

Abstract: Androgenetic alopecia is the most common form of hair loss, affecting 85% of men and 40% of women. Androgenetic alopecia is a disease caused by multiple factors, such as genetics, hormones, and systemic diseases; however, the exact cause remains undetermined. Recent studies have found that it is associated with a high incidence of endocrine diseases and other comorbidities. It may not only be a skin disease but also an early signal of underlying systemic diseases. Effective management requires timely diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 103 publications
0
16
0
1
Order By: Relevance
“…There are studies depicting varied association of AGA with systemic diseases. 19 Systemic diseases such as metabolic syndrome which includes hypertension, diabetes and obesity have been shown to be present concomitantly in patients with AGA. 19 Our study showed co-existence of systemic disease such as coronary artery disease in 3 patients and one patient with AGA with prostate cancer had completed his cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies depicting varied association of AGA with systemic diseases. 19 Systemic diseases such as metabolic syndrome which includes hypertension, diabetes and obesity have been shown to be present concomitantly in patients with AGA. 19 Our study showed co-existence of systemic disease such as coronary artery disease in 3 patients and one patient with AGA with prostate cancer had completed his cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…19 Systemic diseases such as metabolic syndrome which includes hypertension, diabetes and obesity have been shown to be present concomitantly in patients with AGA. 19 Our study showed co-existence of systemic disease such as coronary artery disease in 3 patients and one patient with AGA with prostate cancer had completed his cancer therapy. Patients should be screened for comorbid concomitant metabolic syndrome, for early metabolic control and prevention of hazardous complications thereof.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities associated with PCA remain largely unknown. 20,21 Owing to its low incidence, most retrospective studies on PCA have had small sample sizes, which provide insufficient information for identification of comorbidities. 11,[22][23][24] A recent, large, populationbased study showed that LPP is significantly associated with metabolic syndrome (OR 10.11, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities associated with PCA remain largely unknown 20,21 . Owing to its low incidence, most retrospective studies on PCA have had small sample sizes, which provide insufficient information for identification of comorbidities 11,22–24 .…”
Section: Discussionmentioning
confidence: 99%
“…Przez to wielu badaczy wysnuło tezę, która mówi, że występowanie łysienia androgenowego jest czynnikiem ryzyka zachorowania na Covid -19, lub jego cięższego przebiegu. [22][23] Związek między występowaniem łysienia androgenowego, a ciężkim przebiegiem infekcji koronawirusem, postanowiono nazwać "objawem Gabrina", na cześć pierwszego amerykańskiego lekarza, który zmarł w wyniku ciężkiego przebiegu Covid-19 i od lat chorował na łysienie androgenowe, jednak część naukowców nie jest przekonanych, czy to odpowiedni przejaw wyrazu uznania. [23][24] V Wnioski Wybuch pandemii 3 lata temu zmienił cały świat, mimo upływu tego czasu dalej nie jest dobrze poznana choroba, zdefiniowany został "long Covid" oraz zespół postcovidowy, jednak dalej nie wiadomo jaki wpływ na organizm będzie miał koronawirus w perspektywie kilku lat.…”
unclassified